Equine Umbilical Cord Serum Composition and Its Healing Effects in Equine Corneal Ulceration - Peyrecave-Capo, Xavier; Saulnier, Nathalie; Maddens, Stéphane; Gremillet, Bérengère; Desjardins, Isabelle (Frontiers in Veterinary Science, 2022)
Background: Human autologous serum (AS) and umbilical cord serum (UCS) both contain growth and neurotrophic factors that promote corneal healing. Aim: Our objectives were to compare equine AS and UCS cytokine and growth factor profiles, and to assess the safety and clinical feasibility of the therapeutic use of UCS eye drops in cases of spontaneous complex ulcers. Study design: Prospective pilot study. Methods: Vitamin A, IGF, PDGF-BB, TGF-β1 (ELISA), IL-1β, IL-6, INF-γ, MCP1 concentrations were determined in 10 AS collected from different horses and 10 UCS sampled at delivery. Six client-owned horses presenting with complex non-healing corneal defects of > 5 mm2 were included in a clinical study and treated with conventional therapy and conditioned UCS drops for 8-15 days. Ulcer surface and time to complete epithelialization were recorded. Results: Median concentrations of vitamin A, IGF, PDGF-BB were not significantly different in AS compared to UCS (respectively, 14.5 vs 12.05 µg/mL; 107.8 vs 107.3 pg/mL; 369.1 vs 924.2 pg/mL). TGF-β1 median concentration in UCS was significantly higher than in AS (3245 vs 2571pg/mL) (p=0.04). IL-1β, IL-6, INF-γ, MCP1 concentrations were variable in AS and undetectable in UCS. The corneal median ulcerative area was 37.2 mm2 (6.28-57.14 mm2) and was of 4-186 days duration (median 19 days). All lesions healed within 13-42 days (median 17 days). No adverse effect nor recurrence within one month were noticed. Limitations: The sample size was small. Spontaneous corneal epithelial defects presented with variable clinical characteristics. There were no age-matched control horses to assess corneal healing time and rate. Conclusion and clinical significance: Equine UCS may be beneficial as it contains no pro-inflammatory cytokines and a greater concentration of TGF-β1 compared to AS. Topical UCS appears safe and may potentially be used as an adjunctive therapy for equine complex non-healing ulcers.